KONSEP MANUSIA YANG MENYEJARAH SEBAGAI DASAR PENGEMBANGAN EPISTEMOLOGI PENDIDIKAN ISLAM - Hafidz Hafidz (Jurnal Filsafat "WISDOM", 2008)
AbstractSometimes there are contradictions between social dan individual aspect of people because the social side opens a possibility in developing human autonomy, but also impedes a growth of creativity. This contradictions always accompany the history of human and determine the style of knowledge produced through an education process. In this case, the mediums used to have knowledge and the methods of education must not become aseriously debate matter, but the most important thing to reconsider is the essence of science finding.Keywords: Style of knowledges, Education, Science